Особливості формування системи управління ризиками підприємств агропродовольчої сфери та принципи її реалізації - Головко, Богдан Ігорович; Перевозова, Ірина Володимирівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Стаття присвячена дослідженню особливостей побудови системи управління ризиками підприємств агросфери та принципів її реалізації. Доведено, що управління ризиками є критично важливим у контексті забезпечення ефективності діяльності підприємств цієї сфери, оскільки ця галузь функціонує в умовах високої невизначеності. Визначено, що особливості побудови системи управління ризиками в агропродовольчій сфері зумовлені необхідністю комплексного та адаптивного підходу. Така система має охоплювати всі рівні управління підприємством і включати процеси ідентифікації, аналізу, оцінки та мінімізації ризиків. Встановлено, що реалізація системи управління ризиками повинна ґрунтуватися на низці принципів, серед яких ключову роль, на нашу думку відіграють принципи превентивності, системності, гнучкості та адаптивності, диверсифікації, безперервного моніторингу.

The article is devoted to studying the features of building a risk management system for agrifood enterprises and the principles of its implementation. Risk management is a critically important aspect of agri-food enterprises' activities since this industry operates in conditions of high uncertainty. Dependence on natural and climatic conditions, fluctuations in prices for raw materials and fuel, regulatory restrictions, and global economic and political changes create significant challenges for agrarian businesses and the food industry. It is determined that the features of building a risk management system in the agri-food sector are due to the need for a comprehensive and adaptive approach. Such a system should cover all levels of enterprise management and include the processes of identifying, analyzing, assessing, and minimizing risks. Successful risk management implementation is based on modern information technologies, forecasting methods, and effective management solutions that protect the enterprise from possible losses and the use of risky situations to increase competitiveness.
Features of the formation of a risk management system for agri-food enterprises and the principles of its implementation
Keywords: системи управління; агропродовольча сфера; ефективність; конкурентоспроможність; управління ризиками; принципи; management systems; agri-food sector; efficiency; competitiveness; principles; risks